Unemployment Rate: Regional Economic Growth Moderated by Education Level in Bandung Regency in 2013-2022 - Nababan, Daniel; Sambas Putra, Ivan Gumilar; Hendayana, Yana (Fakultas Pendidikan Ekonomi dan Bisnis, 2023)
West Java Province (Jabar), as one of the regions in Indonesia, has a land area of 35,277.76 km2 with 18 Regency Governments (RG) and 9 City Governments (CG). In the economic stru acture in West Java, the industrial sector had the most considerable contribution, followed by the agricultural sector. Even though the industrial sector enormously contributed to West Java, the Gross Regional Domestic Income (GRDP) level in each district and city government was very different. This research aimed to determine the effect of the unemployment rate on regional economic growth, moderated by the level of education in Bandung Regency. The research method used descriptive and verification methods, with research data for ten years starting 2013-2022, obtained from the Central Statistics Agency (BPS) of West Java Province. We processed data using simple linear regression analysis and moderation tests. The results of the research state that the unemployment rate influenced regional economic growth, and the level of education could moderate the influence of the unemployment rate on regional economic growth in Bandung Regency.